2018
DOI: 10.3347/kjp.2018.56.6.559
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Phylogenetic Analysis of Anaplasma phagocytophilum in Horses in Korea

Abstract: The identification and characterization of pathogenic and zoonotic tick-borne diseases like granulocytic anaplasmosis are essential for developing effective control programs. The differential diagnosis of pathogenic Anaplasma phagocytophilum and non-pathogenic A. phagocytophilum-like Anaplasma spp. is important for implementing effective treatment from control programs. The objective of the present study was to investigate the prevalence of Anaplasma spp. in horses in Korea by nucleotide sequencing and restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The high homology of A. phagocytophilum from different areas (100%) demonstrates the low variation of A. phagocytophilum distributed throughout the ROK. In addition, the A. phagocytophilum sequences detected in ticks during this study demonstrated 100% similarity to those previously detected in infected horses [ 37 ]. Various gene fragments have been used for identification of A. phagocytophilum [ 38 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The high homology of A. phagocytophilum from different areas (100%) demonstrates the low variation of A. phagocytophilum distributed throughout the ROK. In addition, the A. phagocytophilum sequences detected in ticks during this study demonstrated 100% similarity to those previously detected in infected horses [ 37 ]. Various gene fragments have been used for identification of A. phagocytophilum [ 38 ].…”
Section: Discussionsupporting
confidence: 73%
“…Various gene fragments have been used for identification of A. phagocytophilum [ 38 ]. However, other genes, e.g., groEL and msp2 , were shown not to be helpful for the detection of A. phagocytophilum in the ROK [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was the first study reporting the molecular epidemiology of Anaplasmataceae in small ruminants of Uganda, however, further studies using the 16S rRNA and other gene targets related to Anaplasmataceae ( Ali et al., 2017 ; Ringo et al., 2019 ; Seo et al., 2018 ; Shi et al., 2020 ; Yang et al., 2016 ), would pave way for the characterization of Anaplasma infections in both small and large ruminants in Uganda to understand evolutionary changes and sources of variation for improved animal health.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular diagnosis of Anaplasma bacteria is by detection of the 16S rRNA gene ( Ringo et al., 2019 ; Shi et al., 2020 ; Yang et al., 2016 ). This forms the basis of phylogenetic analysis in the Anaplasmataceae ( Seo et al., 2018 ) for insight into genotypic variation and diversity. In Xinjiang, northwest China, a prevalence of 17.6% for A. phagocytophilum, 4.8% for A. bovis and 40.5% for A. ovis shows the importance of these bacteria in small ruminant health ( Yang et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the GroEL and msp2 genes could separately describe A. phagocytophilum. 25 Several studies have demonstrated that the pathogenicity or genotype of A. phagocytophilum would be determined especially by using the groEL gene region. 8,[26][27][28] In the present study, we couldn't unable to replicate horses DNA using groEL fragment, in this way, we couldn't classify A. phagocytophilum with regard to genotype.…”
Section: Discussionmentioning
confidence: 99%